Needs Analysis of Ethnoscience-Based STEM Teaching Materials for the Science Education Program - Santoso, Agus; Mahbubah, Khoiro; Aini, Qonita Qurotul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research is driven by the urgent need to produce university graduates who are not only scientifically competent but also creative and possess a strong appreciation for local wisdom, aligning with the Golden Indonesia 2045 vision and the National Research Master Plan's focus on local knowledge. A preliminary problem analysis identified a gap: the absence of ethnoscience-based STEM (Ethno-STEM) teaching materials specifically designed for university students to enhance their appreciation of local wisdom and creativity. This study aims to analyze the need for Ethno-STEM course materials, which will subsequently be developed into a valid, practical, and effective product. A descriptive mixed-methods approach was employed. Data were collected through document analysis of the semester learning plan, a questionnaire administered to 25 students, and semi-structured interviews with 4 science course lecturers. The results indicate that: (1) The document analysis of the STEM course semester learning plan at UNISLA explicitly mandates the integration of local wisdom and ethnoscience in its learning outcomes. (2) The questionnaire results show that an average of 88% of students expressed a high need for Ethno-STEM teaching materials to improve four key aspects: appreciation of local wisdom, creativity, learning interest, and conceptual understanding. (3) Lecturers confirmed difficulties in finding ready-to-use, structured teaching resources to support the Ethno-STEM project-based learning. The novelty of this study lies in its specific mapping of needs, providing an empirical justification for developing Ethno-STEM teaching materials at the higher education level. It is concluded that there is a valid and urgent need to develop systematic Ethno-STEM teaching materials to support curriculum implementation and enhance the quality of learning in the Science Education Program at UNISLA.